Propylamine Silica-Titania Hybrid Material Modified with Ni(II) as the Catalyst for Benzyl Alcohol to Benzaldehyde Conversion - Dewi Agustiningsih; Nuryono Nuryono; Sri Juari Santosa; Eko Sri Kunarti (Indonesian Journal of Chemistry, 2023)
SiO2-TiO2@propylamine-Ni(II) as the catalyst for the benzyl alcohol oxidation has been synthesized by utilizing rice husk ash as the SiO2 source. This research was started by extracting SiO2 from rice husk ash and continued by synthesizing the SiO2-TiO2 composite using titanium(IV) tetraisopropoxide (TTIP) as TiO2 precursor and PEG-40 as template. The composite functionalization and metal modification were carried out by adding (3-aminopropyl)triethoxysilane (APTES) as the source of propylamine linker and impregnating NiCl2·6H2O as the nickel precursor, respectively. The catalysts were synthesized by varying the ratios between each component within the material. The prepared materials were then characterized using ATR-IR, XRD, XRF, PSA, SAA, AAS, SEM-EDX, HR-TEM, and TGA. The catalyst activity was investigated by applying it to the oxidation reaction of benzyl alcohol to benzaldehyde with H2O2 as the oxidizing agent under sonication system. The obtained products were then analyzed by using GC-MS to quantify the success of the reaction. All characterizations performed in this research generally indicate the success in the synthesis of SiO2-TiO2@propylamine-Ni(II) materials. Under the same condition including at room temperature, 1 h reaction time, and sonication system, the optimal oxidation reaction of benzyl alcohol was reached when SiO2-TiO2@propylamine-Ni(II)5 was used as the catalyst in 98.52% yield.